2020
DOI: 10.13106/jafeb.2020.vol7.no12.1035
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Work Motivation of the Construction Project Manager

Abstract: Project manager plays a very important role in the success of any project. The primary duty of the project manager is to combine the outcomes or results of the various processes and activities of project management into a systematic project management strategy or plan for the project. In the construction industry, a lack of motivation is an urgent problem for many project managers in construction and engineering projects. Lack of motivation affects the quality and productivity of jobs, reducing profits and gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Personal factors include age, working hours, education, etc., while organizational factors include salary, benefits, promotion, colleague relationships, work properties, etc. In the study, Phan et al (2020) (2011), in their study of factors influencing hotel staff's work motivation, found that an increase in work pressure can stimulate stronger motivation among hotel employees, thereby improving their work enthusiasm.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Personal factors include age, working hours, education, etc., while organizational factors include salary, benefits, promotion, colleague relationships, work properties, etc. In the study, Phan et al (2020) (2011), in their study of factors influencing hotel staff's work motivation, found that an increase in work pressure can stimulate stronger motivation among hotel employees, thereby improving their work enthusiasm.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other words, motivation is a factor that creates reasons for action, motivates people to work actively and efficiently, and helps them be as creative as possible (Phan et al, 2020).…”
Section: Motivational Factors In Project Managementmentioning
confidence: 99%
“…Not much can be done by an employee, his status as functional is implementing policies, implementing rules, and executing orders. However, in principle, employees are human beings who have hearts and minds, so they are sensitive to dynamics, sensitive to attitudes and behavior (Pham, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%